Community of Aquatic Macroinvertebrates in an Atlantic Forest Stream, Brazil - Azevedo, Rafael Santos de; Dumas, Leandro; Rodrigues, Daniela; Rezende, Carla Ferreira; Caramaschi, Érica Pellegrini; Mazzoni, Rosana; Nessimian, Jorge (EntomoBrasilis, 2012)
Composition, diversity and density of benthic macroinvertebrates were described based on samples from the four different sites of Rio Mato Grosso, Saquarema, Rio de Janeiro. Biotic and environmental data were obtained in January 2006 in microhabitats with different substrates. A total of 5.605 specimens of the 28 insect families and two crustaceous families are sampled. The lowest values of richness, diversity, equitability and density were observed in low altitude sites. The highest diversity and density values were observed in litter substrate, while sand substrate showed lower values of these parameters. Estrutura da Comunidade de Macroinvertebrados Aquáticos de um Riacho de Mata Atlântica, Brasil Resumo. A composição, diversidade e densidade de macroinvertebrados bentônicos foram descritas a partir de amostras provenientes de quatro localidades distintas do Rio Mato Grosso, Saquarema, Rio de Janeiro. Os dados bióticos e abióticos foram obtidos em janeiro 2006 em microhabitats com diferentes tipos de substrato. Foi amostrado um total de 5.605 espécimes de 28 famílias de insetos e duas de crustáceos. Os menores valores de riqueza, diversidade, equitabilidade e densidade foram registrados nas localidades de menor altitude. Folhiço foi o substrato com maiores valores de diversidade e densidade, enquanto areia apresentou os menores valores desses parâmetros.